2021
DOI: 10.1002/cpdd.1042
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Pharmacokinetics, and Pharmacodynamics of the ADAMTS‐5 Inhibitor GLPG1972/S201086 in Healthy Volunteers and Participants With Osteoarthritis of the Knee or Hip

Abstract: GLPG1972/S201086 is a disintegrin and metalloproteinase with thrombospondin motif-5 (ADAMTS-5) inhibitor in development as an osteoarthritis disease-modifying therapy. We report the safety, tolerability, pharmacokinetics, and pharmacodynamics (turnover of plasma/serum ARGS-aggrecan neoepitope fragments [ARGS]) of GLPG1972 in 3 randomized, double-blind, placebo-controlled phase 1 trials. Study A, a first-in-human trial of single (≤2100 mg [fasted] and 300 mg [fed]) and multiple (≤1050 mg once daily [fed]; 14 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…GLPG1972 was well tolerated at all doses (up to 2100 mg once daily) in phase I clinical trials. 26 Thus, despite the slightly higher activity of 18 in inhibition of MMP2, MMP8, and MMP12 when compared to GLPG1972, the imperfect protease selectivity from inhibition of MMP12/8/2 does not raise safety and toxicity "red flags" on compound 18.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLPG1972 was well tolerated at all doses (up to 2100 mg once daily) in phase I clinical trials. 26 Thus, despite the slightly higher activity of 18 in inhibition of MMP2, MMP8, and MMP12 when compared to GLPG1972, the imperfect protease selectivity from inhibition of MMP12/8/2 does not raise safety and toxicity "red flags" on compound 18.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, GLPG1972 did not meet its primary clinical endpoints in phase II clinical studies. Both GLPG1972 and ADAMTS-5 nanobody therapies were well tolerated and generally safe. , …”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Research on another proteinase known as aggrecanase (specifically ADAMTS5) as a potential contributor to the progression of osteoarthritis (OA) led to the exploration of GLPG1972/S201086, a drug acting as an ADAMTS5 inhibitor. In a phase I clinical trial, this drug demonstrated a favorable safety profile and effectively decreased aggrecanase activity [33]. However, the results from the phase II clinical trial, published in 2023, revealed that there was no significant reduction in cartilage loss compared to the placebo group [34].…”
Section: Proteinase Inhibitorsmentioning
confidence: 99%
“…The enzyme A disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS-5) is involved in the degradation of aggrecan, which is a critical proteoglycan and building block of cartilage. ADAMTS-5 induces cartilage degradation and has been reported to be highly expressed in patients with OA [97,98]. There have been several attempts in preclinical models to inhibit ADAMTS-5, but often with safety concerns.…”
Section: Inhibition Of Catabolic Factorsmentioning
confidence: 99%